War Violence in the Pre-Modern World - Gilhaus, Lennart, (History of Warfare ;, 2026)
Physical violence lies at the core of war. This volume explores the diverse manifestations of violence in pre-modern societies, from the trophy heads of the pre-Hispanic Andes to the tactics of Mongol conquerors in Central Asia and the battlefields of medieval Europe. Adopting a global historical perspective, it examines how war violence was perceived across different cultures and identifies potential cross-cultural patterns in its use and understanding. Contributors are Ali Anooshahr, Elizabeth Arkush, David S. Bachrach, Martin Clauss, R. Alan Covey, Philip Dwyer, Karl F. Friday, Lennart Gilhaus, Hendrik Hess, Beatrice Forbes Manz, Jürgen Paul, Stefanie Rüther, Beth K. Scaffidi, and Daniel F. Schley.